Aliphatic Acylhydrazides as Effective Alkylating Agents for the Copper-Catalyzed Oxidative Cyclization of N-Arylacrylamides - Xie, Dong; Tian, Ren-Gui; Liao, Jia-Jia; Tian, Shi-Kai (Synthesis, 2023)
An unprecedented use of readily accessible aliphatic acylhydrazides as alkylating agents has been demonstrated in the copper-catalyzed tandem alkylation/cyclization of N-arylacrylamides. A range of aliphatic acylhydrazides smoothly participated in the oxidative 5-exo-trig cyclization of N-arylacrylamides with CuCO3 as the catalyst and DTBP as the oxidant, delivering structurally diverse 3,3-dialkyloxindoles in moderate to good yields. This study paves the way for the synthetic applications of aliphatic acylhydrazides as alkyl radical precursors.
Keywords: acylhydrazide; N-arylacrylamide; oxindole; alkylation; copper; oxidative cyclization